On Marx and accounting: An empirical study of the transformation of values into prices of production in the Brazilian contemporary economy, 2010-2022 - Leonardo Segura Moraes; Raquel de Azevedo (PSL Quarterly Review, 2024)
The purpose of this paper is to present some notes on the contemporary Brazilian economy between 2010 and 2022, translating items from the value added statement (VAS) and the balance sheet of a sample of 48 companies that make up the Bovespa Index (Ibovespa, in Portuguese) portfolio into Marxist economic theory. The information was obtained from InvestSite (https://www.investsite.com.br/) and Economatica (https://economatica.com/) databases. In this sense, we observed some general trends and countertrends of real competition in the Brazilian economy, based on the empirical formulation of the concepts of constant capital, variable capital, surplus-value, turnover of capital, cost-price, price of production, rate of profit, and rate of surplus-value. In this way, we hope to contribute to a research agenda on the criteria for production and appropriation of surplus-value in Brazil, as well as to use the Marxian procedure of transformation of values into prices of production as a macroeconomic tool.
Keywords: B51; E11; M41; P12; 330; Competition; Brazilian economy; Marx; Accounting